2002
DOI: 10.1021/jm0111301
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Biological Evaluation of a New Family of Potent Modulators of Multidrug Resistance:  Reversal of Multidrug Resistance of Mouse Lymphoma Cells by New Natural Jatrophane Diterpenoids Isolated from Euphorbia Species

Abstract: The effects of 15 jatrophane diterpene polyesters (1-3 and 5-16) isolated from lipophilic extracts of Euphorbia serrulata, E. esula, E. salicifolia, and E. peplus (Euphorbiaceae) on the reversion of multidrug resistance of mouse lymphoma cells were examined. The structures of five new compounds (1-5) were elucidated by spectroscopic methods, including HRFABMS, ESIMS, (1)H-(1)H homonuclear and (1)H-(13)C heteronuclear correlations, long-range correlation spectra, and NOESY experiments. The stereochemistry and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 17 publications
5
94
0
Order By: Relevance
“…In previous reports, we have described the isolation and conformation elucidation of several diterpenes (3,4,6) from E. lathyris by X-ray experiment. 23,24 Their bioactivities together with two lathyrane diterpenes-Euphorbia factor L 7a (1) and Euphorbia factor L 7b (2) as potent inhibitors to P-gp were reported at this time.…”
Section: Biological Evaluation and Structure-activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, we have described the isolation and conformation elucidation of several diterpenes (3,4,6) from E. lathyris by X-ray experiment. 23,24 Their bioactivities together with two lathyrane diterpenes-Euphorbia factor L 7a (1) and Euphorbia factor L 7b (2) as potent inhibitors to P-gp were reported at this time.…”
Section: Biological Evaluation and Structure-activity Relationshipsmentioning
confidence: 99%
“…The discovery of jatrophane diterpenes from Euphorbia genus as a series of potent modulators of P-gp has led to a new favor in research of this genus. 6 Euphorbia belonging to Euphorbiaceae family is widely distributed in China and has been used as traditional medicine in many countries to treat cancer and warts. 7 Many chemical studies on Euphorbia species were focused greatly on the components of skin-irritant compounds, mainly consist of ingenane tigliane or daphnane skeletons.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] The simplest hydrolyzable tannin, gallotannin, is a compound of polygalloyl esters of glucose. Gallotannins from other species have been studied to exhibit diverse biological effects ranging from anti-inflammation to antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Linear correlation was found between the toxicity and increased accumulation of doxorubicin however the cells were exposed to higher concentration of Euphorbia species have been used in traditional medicine in many countries to treat cancer and warts (140). Besides the presence of highly skin-irritant compounds (phorboids) (141,142), Euphorbia species are of further considerable interest owing to a large diversity of structurally unique and non-irritant jatrophane and lathyrane diterpenoid constituents, which have been considered to be potent modulators of MDR (143,144). Our research group previously reported that extracts containing macrocyclic diterpenes may reverse MDR by inhibiting P-gp in human mdr1 gene-transfected mouse lymphoma cells (114)(115)(116)).…”
Section: D Di Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%